Gambaran Penyimpanan Obat Di Apotek “X” Kabupaten Banyuwangi Tahun 2022 - Anung kustriyani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Introduction: Storage is one of the management activities. Storage is the activity of storing and maintaining pharmaceutical products in a safe place and avoiding theft and physical disturbance. Storage is carried out to ensure quality, avoid irresponsible use, maintain availability, and facilitate the search and control of pharmaceutical products. Methods: The method used in this research is observational.. The resulting data is descriptive qualitative. Results: Data collection using interviews and observations based on observation sheets made by researchers. In drug storage, there are shelves or display cases. Storage of drugs on shelves alphabetically and by dosage form. Medicines containing precursors are stored separately from other classes of drugs. The temperature for storing the drug is adjusted to the temperature stated on each drug package. For drugs with special storage temperatures, the drugs are stored in the refrigerator. The drug dispensing method uses the First Expired First Out system. LASA and high alert drugs are stored together and close to other drugs. Storage of expired drugs is placed in a separate cupboard before the drugs are destroyed. Conclusion: Drug storage is arranged in a display case, according to alphabetical order, dosage form, and FEFO.